Strategi Peningkatan Sistem Kesehatan Ternak Berkelanjutan di Lahan Kering - Alfonsus I. Malo; Gustaf Oematan (Animal Agricultura, 2026)
Dryland regions present specific challenges in livestock management due to limited feed availability, water scarcity, high disease pressure, and extreme environmental conditions. This study aims to formulate strategies for improving sustainable livestock health through an integrated approach combining feed management, affordable technology, biosecurity, and institutional support. The research employs an in-depth literature review of empirical studies related to livestock health management, forage quality, sanitation, and environmental adaptation in dryland areas. The findings show that continuous access to high-quality feed through the use of drought-tolerant legumes, forage conservation, and household forage gardens can improve livestock immunity and reduce disease risks. The application of biosecurity measures, vaccination, and parasite control based on sanitation significantly reduces the prevalence of infectious diseases. In addition, affordable technologies such as temperature sensors, IoT-based monitoring, digital health record systems, and low-cost ventilation improve early detection accuracy and management efficiency. The success of livestock development in dryland regions is also influenced by government and institutional support through the provision of veterinary services, training, subsidies, and mentoring programs. Therefore, sustainable livestock health systems in dryland environments require the integration of nutrition, environmental management, technology, and policy to enhance livestock resilience and farmer welfare.